Religiusitas, Kepuasan Pelayanan, Dan Pengaruhnya Terhadap Loyalitas Nasabah Bank Syariah Di Kota Surabaya (Analisis Regresi Purposed Mediator dengan Bootstrap Matrix) - Nurlaili Adkhi Rizfa Faiza (Universitas Islam Lamongan, 2022)
High customer loyalty can indicate the success of Islamic banks in line with increasingly fierce business competition between financial institutions and banks. This study aims to examine and analyze the relationship between bank services, customer satisfaction, one's religiosity, and customer loyalty of Islamic banks in the city of Surabaya. Using a research sample of Islamic bank customers who domiciled in Surabaya, this study uses a quantitative approach with a purposed mediator regression analysis with Bootstrap Matrix. The results showed that a person's religiosity and service quality of Islamic banks had a positive and significant effect on their loyalty as customers in Islamic banks. Then, the effect of service on customer loyalty, which is moderated by satisfaction, shows a positive but not significant effect. With the less significant effect of service on loyalty moderated by satisfaction, along with the increasingly fierce business competition between institutions and banks, Islamic banks need to improve the quality of services provided to customers and prospective customers to be able to compete with other financial institutions to obtain satisfaction and maintain customer loyalty. Finally, the results of the simultaneous test show that religiosity and service quality (moderated by customer satisfaction) have a positive and significant effect on customer loyalty in sharia banking in Surabaya.